Situation Report: Czechoslovakia, 21 October 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. An Overview / by Peter Martin Personnel Changes in the CC Presidium and Secretariat / by Jiri Pehe The New Federal Government / by Jiri Pehe New Civic and Political Groups / by Jiri Pehe Dissident Group Promoting Friendship with USA Expands / by Jiri Pehe New Group Issues Program for Democracy in Czechoslovakia / by Vladimir Kusin Bush and Dukakis Give Interview to Dissident Periodical / by Vladimir Kusin Relations with Israel / by Jan Obrman Plans to Ease Travel to the West / by Jiri Pehe